2015 12th International Bhurban Conference on Applied Sciences and Technology (IBCAST) 2015
DOI: 10.1109/ibcast.2015.7058538
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of aberrant aerodynamic behavior of wrap-around fins in collation with planar fins

Abstract: The anomalistic aerodynamic behavior of wrap around fins has kept the researchers engrossed in devising new design methods and analysis techniques. Rolling moment at zero incidence angle, induced forces and moments due to fin curvature, roll reversal phenomenon, static side moment and Magnus side moment are the main aggravations that make their aerodynamics more complex when compared with the planar fins. The present research effort provides a deep insight and explanation for this uncertain aerodynamics associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Their investigations demonstrated that the two fins differ in resulted rolling angles only, with other aerodynamic properties being mostly the same. Omar et al 12 further studied the aerodynamic behavior of displaced WAFs to that of flat fins. They illustrated that, at zero angle of attack, the pressure is different on either sides of the WAF, as compared to similar pressures on either sides of the flat fin.…”
Section: Introductionmentioning
confidence: 99%
“…Their investigations demonstrated that the two fins differ in resulted rolling angles only, with other aerodynamic properties being mostly the same. Omar et al 12 further studied the aerodynamic behavior of displaced WAFs to that of flat fins. They illustrated that, at zero angle of attack, the pressure is different on either sides of the WAF, as compared to similar pressures on either sides of the flat fin.…”
Section: Introductionmentioning
confidence: 99%